2013
DOI: 10.1038/nmeth.2763
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the feasibility of large-scale development of standardized assays to quantify human proteins

Abstract: The successful application of MRM in biological specimens raises the exciting possibility that assays can be configured to measure all human proteins, resulting in an assay resource that would promote advances in biomedical research. We report the results of a pilot study designed to test the feasibility of a large-scale, international effort in MRM assay generation. We have configured, validated across three laboratories, and made publicly available as a resource to the community 645 novel MRM assays represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
194
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(198 citation statements)
references
References 59 publications
4
194
0
Order By: Relevance
“…For the reproducible and accurate quantification of tryptic peptides in complex proteome digests, the S/MRM technique has been shown to reach a high dynamic range of about five orders of magnitude, as well as excellent interlaboratory reproducibility, with a median coefficient of variation (CV) of ϳ5% (99). Similar analytical performances were also observed using the PRM approach (100 -102).…”
Section: Identification and Quantification Of Mhc-associated Peptidesmentioning
confidence: 77%
“…For the reproducible and accurate quantification of tryptic peptides in complex proteome digests, the S/MRM technique has been shown to reach a high dynamic range of about five orders of magnitude, as well as excellent interlaboratory reproducibility, with a median coefficient of variation (CV) of ϳ5% (99). Similar analytical performances were also observed using the PRM approach (100 -102).…”
Section: Identification and Quantification Of Mhc-associated Peptidesmentioning
confidence: 77%
“…The bulk of recent work has focused on candidate discovery and overcoming the associated challenges related to tissues and bodily fluids. Targeted proteomics can be used to validate biomarkers found in a project's discovery phase across many patient samples with high accuracy and reproducibility 29, 74. Cima and coworkers successfully applied this strategy by initially using shotgun data to establish a protein list of 44 candidates.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Targeted proteomics is best suited to meet these needs. Multiple studies clearly demonstrated the reproducibility of SRM‐MS across laboratories 29, 30. SRM‐MS has been applied to quantify protein levels of liver tissue across 40 strains of BDX mouse 31 and quantitative trait analysis (QTL) of 78 Saccharomyces cerevisiae strains 32.…”
Section: Introductionmentioning
confidence: 99%
“…High quality and crude isotopically labeled standard peptides with C-terminal 15 N-and 13 C-labeled arginine and lysine residues (HeavyPeptide AQUA TM Ultimate at 5 pmol/l Ϯ 5% and PEPotecs TM ) were synthesized by Thermo Fisher Scientific (Bremen, Germany). C 18 Sep-Pak cartridges (Sep-Pak Vac, 1 ml, 50 mg, tC18) were obtained from Waters (Milford, MA), and all other reagents and chemicals were purchased from Sigma-Aldrich. All buffers were prepared with ultrapure water.…”
Section: Chemicalsmentioning
confidence: 99%